2D MoS2/graphene composites with excellent full Ku band microwave absorption. Issue 108 (8th November 2016) - Wang, Xiaoxia; Zhang, Wenling; Ji, Xuqiang; Zhang, Baoqin; Yu, Mingxun; Zhang, Wei; Liu, Jingquan
Abstract : 2D MoS2 /graphene composites were proved to be promising full Ku band MA materials due to their superb high dielectric loss. Abstract : Increasing attention has been focused on microwave absorption (MA) performance in the Ku band (12.4–18.0 GHz) due to the rapid development of radar, military aircraft and satellite communications. In this work, 2D heterostructure MoS2 /graphene composites were proven to be promising full Ku band MA materials due to their superb characteristics of high dielectric loss, low density, large surface area and good thermal stability. By a simple one step solvothermal method, MoS2 /graphene composites were successfully obtained, and the matched 2D structure between MoS2 and graphene could generate synergistic effects and maximize the MA properties. Only with 30 wt% of the as-prepared MoS2 /graphene composites, excellent MA properties in wide frequency bands were obtained. An optimal reflection loss (RL) value of −41.9 dB was obtained at 16.1 GHz with a thickness of 2.4 mm and the RL values exceeding −10 dB were achieved in the whole Ku band (12.2–18.0 GHz) with a thickness of 2.6–3.0 mm.